Performance of imaging professionals and civil liability (Research, Society and Development, 2025)
This article aims to clarify the scope of action of health professionals who work in diagnostic and therapeutic services using images. The research is of the documentary type based on legislation related to the professional practice of health professionals who work in the area (laws, decrees, resolutions of class bodies) obtained from the websites of the Brazilian Legislative Branch; and from the class councils of related professionals; in the theoretical basis and discussion, scientific articles were researched in journal databases,  such as SciElo, PubMed and scientific publishers for the elaboration of the narrative review. The survey allowed the elaboration of legal aspects on the professional performance of technicians and technologists in radiology, biomedical doctors, physicians, dentists, veterinarians and medical physicists, professionals recognized in Brazilian legislation as related to Imaging. This area of professional activity includes different techniques, diagnostic and/or therapeutic procedures that expressed to the attending physician and the patient through graphic documentation, body images or functional aspects of organic metabolism. These professionals, within the scope of their legal attributions, may be liable to civil or criminal liability because of the technical intervention performed or diagnostic error.